Revised taxonomic status of Scythia Kiritchenko, 1938 and Mohelnia Šulc, 1941 (Hemiptera: Coccomorpha: Coccidae: Eriopeltinae) - Chen, Lijie; Xing, Jichun (Zootaxa, 2021)
The soft scale insect genus Scythia (Hemiptera: Coccomorpha: Coccidae) was established by Kiritchenko (1938) with the type species Scythia craniumequinum Kiritchenko, 1938 from Ukraine. Later, Borchsenius (1957) placed Mohelnia Šulc, 1941 (type species: Mohelnia festuceti Šulc, 1941) as a junior subjective synonym of Scythia Kiritchenko, 1938, and proposed new combination: Scythia festuceti (Šulc, 1941). Ben-Dov (1993) followed Borchsenius (1957) in treating Mohelnia as a junior synonym of Scythia.